[PP.22.02] DEFICIENCY OF PURINERGIC P2X7 RECEPTOR PROTECTS AGAINST PROGRESSION OF CHRONIC RENAL INJURY. (September 2016) - POTTHOFF, S.; Tiedge, M.; Srugies, F.; Bockmeyer, C.; Rump, L.C.; Vonend, O.
Abstract : Objective: Chronic kidney disease is defined as a progressive loss of renal function often leading to renal replacement therapy. As a member of ionotropic ATP-gated receptors the P2X7-receptor (P2X7R) is detected on immune cells like lymphocytes, macrophages and dendritic cells. It is known that P2X7Rs mediate Ca2+ and Na+-influx in signal transduction and the release of pro-inflammatory cytokines (Il1β and Il18). In this study, we test whether P2X7-receptor deficiency in FVB mice prevents progression of chronic renal injury after subtotal nephrectomy (SNX). Design and method: SNX was performed in wild type and P2X7R knock out mice and assessment of physiological parameters was performed at different time points for 35 days. Kidneys were removed on day 35 for further assessment with real-time PCR (RT-PCR), Western Blot (WB) and histological staining. Results: On day 35, remnant-kidney-mass was significantly lower in P2X7R-KO mice compared to controls. In P2X7R-KO mice urine urea level was significantly higher on day 5 and day 35, urine creatinine level was higher throughout day 5 to 35 and albumin-creatinine ratio was lower throughout day 10 to 35 compared to controls. Systolic blood pressure was significantly lower in P2X7R-KO mice. RT-PCR analysis showed reduced expression of collagen1, MCP-1 and NFκB in P2X7R-KO mice. WB showed a significantly lower level of collagen1 in P2X7R-KO mice. PAS staining showed a significantly reduced number of sclerosed glomeruli in P2X7R-KO mice compared to controls. Conclusions: These data indicate reduced compensatory hypertrophy in P2X7R-KO kidneys after SNX. Urine samples suggest a preserved tubulo-interstitial function in P2X7R-KO mice. Despite small difference in systolic blood pressure, heart weight showed no difference, indicating blood pressure independent effects on organ injury. Reduced collagen1-expression in RT-PCR and WB support lower fibrosis, possibly contributing to reduced hypertrophy. The reduced number in sclerosed glomeruli and reduced proteinuria indicate a preserved glomerular function. Reduced inflammatory response indicated by lower MCP-1 and NFκB expression are likely the underlying cause for the attenuated progression of renal injury in this model. Therefore, P2X7 deficiency protects against progression of chronic renal injury by reduced inflammatory response resulting in reduced interstitial fibrosis and glomerulosclerosis.